Forest Management in the Interface: Water Management - Susan W. Vince; Martha C. Monroe (EDIS)
Revised! FOR-181, a 6-page fact sheet by Susan W. Vince and Martha C. Monroe, describes the role of forests in the water cycle and the hydrological effects of land development, and introduces four strategies for lessening the negative hydrological effects of urbanization: protecting forests, reducing impervious surface cover, controlling sources of pollutants, and managing stormwater runoff. Includes references. Published by the UF School of Forest Resources and Conservation, July 2008.